2022
DOI: 10.1186/s12876-022-02466-9
|View full text |Cite
|
Sign up to set email alerts
|

Fully covered self-expandable metal stent for intraprocedural or late-diagnosed Type-II endoscopic retrograde cholangiopancreatography-related perforations

Abstract: Background Perforations related to endoscopic retrograde cholangiopancreatography (ERCP) are rare but life-threatening complications. The treatment of Type-II-periampullary perforations that develop during endoscopic sphincterotomy remains a topic of discussion. This study aimed to evaluate the usefulness of fully covered self-expanding metal stenting (FCSEMS) for treating Type-II perforations. Methods The files of all patients who underwent the ER… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Recent studies have demonstrated the successful treatment of Stapfer type II perforations by inserting covered metal stents instead of surgical treatment [ 3 , 9 ]. In theory, the covered metal stent could block the leakage of fluid from the lesion into the retroperitoneal cavity by closing the perforated hole, thereby reducing the inflammatory response and accelerating healing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recent studies have demonstrated the successful treatment of Stapfer type II perforations by inserting covered metal stents instead of surgical treatment [ 3 , 9 ]. In theory, the covered metal stent could block the leakage of fluid from the lesion into the retroperitoneal cavity by closing the perforated hole, thereby reducing the inflammatory response and accelerating healing.…”
Section: Discussionmentioning
confidence: 99%
“…In theory, the covered metal stent could block the leakage of fluid from the lesion into the retroperitoneal cavity by closing the perforated hole, thereby reducing the inflammatory response and accelerating healing. Bozbiyik et al retrospectively compared SEMS (fully covered type, n = 19) with conventional treatment (n = 9) in type II ERCP perforation [ 9 ]. In this study, the conventional treatment included NPO, intravenous antibiotic administration, and close monitoring without other biliary drainage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Endoscopic negative pressure therapy may help with secondary wound healing [15,16]. The use of fully covered self-expandable metal stents (FC-SEMS) for iatrogenic perforations related to ERCP is another treatment option used to seal the defect [17].…”
Section: Introductionmentioning
confidence: 99%